DEVELOPMENT AND VALIDATION OF NEW RP-UPLC METHOD FOR THE QUANTITATIVE DETERMINATION OF OLANZAPINE IN TABLET DOSAGE FORM - RAJA ABHILASH PUNUGOTI; JUPALLY, VENKATESHWAR RAO (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective: to develop and validate a new very rapid, sensitive, reverse phase Ultra Performance Liquid Chromatography (RP-UPLC) technique for the estimation of Olanzapine in dosage form, as there is no official monograph & no analytical method by UPLC. Methodology: Chromatographic separation was achieved on a Waters Acquity HSS T-3 C18 column (100 Ã— 2.1 mm, 1.8Î¼m) using an isocratic method with mobile phase composed of Potassium di-hydrogen phosphate: methanol in the ratio 60:40 v/v. The flow rate was 0.8 ml/min, temperature of the column was maintained at ambient and detection was made at 228 nm. The run time was as short as 6 min. The developed method was validated according to the International Conference on Harmonization (ICH) guidelines with respect to linearity, accuracy, precision, specificity and robustness. Results: The developed method was linear for Olanzapine from 10 - 50 Î¼g/ml and the linear regression obtained was > 0.999. Precision, evaluated by intra- and inter-day assays had relative standard deviation (R.S.D) values within 1.5 %. Recovery data were in the range 98.2% to 100.9% with R.S.D. values < 1.5 %. Conclusion: The method is precise, accurate, linear, robust and fast. The short retention time of 2.433 min allows the analysis of a large number of samples in a short period of time and, therefore, should be cost-effective for routine analysis in the pharmaceutical industry.